COMMUNITY PARTICIPATION IN SCHOOL MANAGEMENT: PERSPECTIVE AND PRACTICES IN ASSAM (International Journal of Food and Nutritional Sciences, 2022)
There are influence that favour attractive the participation of the community in the management of schools, mainly those that are government-controlled or aided. Such participation in education is seen as a way to boost resources, improve responsibility of schools to the community they serve, ensure a more commercial use of resources and, more importantly, be responsive to local needs. In fact such participation is expected to improve equitable access, retention, quality and presentation of schools.Community participation is not a new method or practice. Historically, communities have played an important role in the provision and management of schools in different parts of the world and these were mediated through church or caste/ethnic associations or civil society groups. In many parts of India too, parents or members of the community have provided property or other resources for the setting up of government schools. It is on the basis of this that development organisations are actively advocating well thought-out community participation in the management of schools.